2006
DOI: 10.4103/0970-4388.27895
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitroevaluation of pH variations in calcium hydroxide liners

Abstract: The purpose of this present study was to determine the pH changes of five different commercially available calcium hydroxide liners and variations of pH at different time intervals. The following commercially available materials were investigated: Dycal (LD Caulk); Calcimol (Vocco Products); calcium hydroxide powder (Deepti Products); Calcimol LC (Vocco Products); Lime-Lite (Pulpdent Corporation). Five samples were prepared from each liner. The pH measurements were recorded at time intervals of 1 h, 24 h, 3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The conditioned media obtained from Dycal ® had pH values of 9.80-10.86 over the 168-h (7 days) duration of this assay. This finding was in agreement with previous reports 25,[38][39][40][41][42][43] . The conditioned media obtained from PCFA also maintained high alkaline levels, with pH values of 10.57-11.72, which were significantly higher than those of Dycal ® during the 168-h (7 days) duration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The conditioned media obtained from Dycal ® had pH values of 9.80-10.86 over the 168-h (7 days) duration of this assay. This finding was in agreement with previous reports 25,[38][39][40][41][42][43] . The conditioned media obtained from PCFA also maintained high alkaline levels, with pH values of 10.57-11.72, which were significantly higher than those of Dycal ® during the 168-h (7 days) duration.…”
Section: Discussionsupporting
confidence: 83%
“…This difference may be due to the different amount of hydroxyl ions released from each material. The higher pH value may have some advantages in neutralization of the acid at the site of inflammation, antibacterial effect, and stimulation of the repair and dentin bridge formation in the exposed pulp 25,36,42,44) . The ISO standard for a pulp capping material has not been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix constituents can affect the availability of therapeutic agents, in contrast to conventional, non‐matrix‐associated materials. It has been shown that chemically cured materials have a more alkaline effect compared with light‐cured capping materials . In the present study, all materials – and in particular TH – were able to increase the pH of the medium.…”
Section: Discussionsupporting
confidence: 51%
“…The isolation of Lactobacilli is not surprising, taking into consideration the fact that this bacteria can thrive at even a low pH of 4, which is the average pH in deep carious lesions. The cariogenicity of Streptococci and Peptostreptococci in gnotobiotic rats is well established 19 . Peptostreptococcus, Bacteroides and Fusobacterium have also been isolated from carious dentin by other researchers and the findings of our study are in accordance to them 11,10 .…”
Section: Discussionmentioning
confidence: 99%
“…This material also contains a fluoride salt that is known to have antimicrobial action. The pH of LimeLite after 7 days has been shown to be 10-11, which could also be a contributory factor for its antimicrobial action 19 .…”
Section: Discussionmentioning
confidence: 99%